SRC and MEK Co-inhibition Synergistically Enhances the Anti-tumor Effect in Both Non-small-cell Lung Cancer (NSCLC) and Erlotinib-Resistant NSCLC - Yuan, Man; Xu, Lin-feng; Zhang, Juan; Kong, Si-yuan; Wu, Man; Lao, Yuan-zhi; Zhou, Hua; Zhang, Li; Xu, Hongxi (Frontiers in Oncology, 2019)
Non-small-cell lung cancer (NSCLC) is the predominant form of lung cancer, and it is regulated by a complex signal transduction network. Single-agent targeted therapy often results in acquired resistance, which leads to treatment failure. In this study, we demonstrated that a combination of the kinase inhibitors trametinib and bosutinib can synergistically suppress the growth of NSCLC by inhibiting both the MAPK and SRC pathways. The combination was profiled against a panel of 22 NSCLC cell lines, including one erlotinib-resistant cell line, and this combination was found to show synergistic effects against 16 cell lines. NSCLC cell lines (HCC827, HCC827-erlotinib-resistant, and H1650) were treated with trametinib, bosutinib, or a combination of these drugs. The drug combination inhibited colony formation and induced cell apoptosis. A mechanism study showed that the phosphorylation of multiple kinases in the EGFR signaling pathway in NSCLC was down-regulated. In addition, the combination significantly attenuated tumor growth of HCC827 xenografts with low toxicity. Our findings provide a theoretical basis for further study of the combination of MAPK and SRC pathway inhibitors in NSCLC, especially in the treatment of erlotinib-resistant NSCLC.